Rigid crosslinking of the CD3 complex leads to superior T cell stimulation - Nelson, Alfreda D.; Wang, Liangyu; Laffey, Kimberly G.; Becher, Laura R. E.; Parks, Christopher A.; Hoffmann, Michele M.; Galeano, Belinda K.; Mangalam, Ashutosh; Teixeiro, Emma; White, Tommi A.; Schrum, Adam G.; Cannon, John F.; et al. (Frontiers in Immunology, 2024)
Functionally bivalent non-covalent Fab dimers (Bi-Fabs) specific for the TCR/CD3 complex promote CD3 signaling on T cells. While comparing functional responses to stimulation with Bi-Fab, F(ab')2 or mAb specific for the same CD3 epitope, we observed fratricide requiring anti-CD3 bridging of adjacent T cells. Surprisingly, anti-CD3 Bi-Fab ranked first in fratricide potency, followed by anti-CD3 F(ab')2 and anti-CD3 mAb. Low resolution structural studies revealed anti-CD3 Bi-Fabs and F(ab')2 adopt similar global shapes with CD3-binding sites oriented outward. However, under molecular dynamic simulations, anti-CD3 Bi-Fabs crosslinked CD3 more rigidly than F(ab')2. Furthermore, molecular modelling of Bi-Fab and F(ab')2 binding to CD3 predicted crosslinking of T cell antigen receptors located in opposing plasma membrane domains, a feature fitting with T cell fratricide observed. Thus, increasing rigidity of Fab-CD3 crosslinking between opposing effector-target pairs may result in stronger T cell effector function. These findings could guide improving clinical performance of bi-specific anti-CD3 drugs.